Partial Scene Text Retrieval - Wang, Hao; Liao, Minghui; Xie, Zhouyi; Liu, Wenyu; Bai, Xiang (IEEE transactions on pattern analysis and machine intelligence, 2025)
The task of partial scene text retrieval involves localizing and searching for text instances that are the same or similar to a given query text from an image gallery. However, existing methods can only handle text-line instances, leaving the problem of searching for partial patches within these text-line instances unsolved due to a lack of patch annotations in the training data. To address this issue, we propose a network that can simultaneously retrieve both text-line instances and their partial patches. Our method embeds the two types of data (query text and scene text instances) into a shared feature space and measures their cross-modal similarities. To handle partial patches, our proposed approach adopts a Multiple Instance Learning (MIL) approach to learn their similarities with query text, without requiring extra annotations. However, constructing bags, which is a standard step of conventional MIL approaches, can introduce numerous noisy samples for training, and lower inference speed. To address this issue, we propose a Ranking MIL (RankMIL) approach to adaptively filter those noisy samples. Additionally, we present a Dynamic Partial Match Algorithm (DPMA) that can directly search for the target partial patch from a text-line instance during the inference stage, without requiring bags. This greatly improves the search efficiency and the performance of retrieving partial patches. We evaluate the proposed method on both English and Chinese datasets in two tasks: retrieving text-line instances and partial patches. For English text retrieval, our method outperforms state-of-the-art approaches by 8.04% mAP and 12.71% mAP on average, respectively, among three datasets for the two tasks. For Chinese text retrieval, our approach surpasses state-of-the-art approaches by 24.45% mAP and 38.06% mAP on average, respectively, among three datasets for the two tasks.